Gender differences in lower facial soft tissue thickness among different skeletal patterns, based on soft tissue cephalometric analysis - Almustafa Alhumadi; Thaer Jaber Al-Khafaji; Ali Mihsen Hussein Alyassiri; Wisam W Alhamadi (Wolters Kluwer Medknow Publications, 2022)
OBJECTIVE: Lower face soft tissue thickness and dentoskeletal features form the lower facial profile. Sagittal skeletal malocclusions with varying degrees of soft tissue thickness in males and females were herein examined using soft tissue cephalometric radiography. METHODS: Based on their dentoskeletal correlations, a total of 160 lateral cephalometric radiographs of adult males and females (n = 80) seeking orthodontic treatment were classified as class I (n = 40), class II division 1 (n = 40), class II division 2 (n = 40), or class III (n = 40). Holdaway analysis was used to assess soft tissue thickness in seven linear parameters. RESULTS: In class I, class II division 1, class II division 2, and class III dentoskeletal connections, males exhibited larger soft tissue thickness. They have an average lower lip thickness, chin depth H, and depth V for class I males. Males and females differed from one another when it came to the thicknesses of the upper and the lower lips. These lip thicknesses as well as the chin's width differed more between men and women in class II division 1. Except for upper lip strain, all measures in the class II division 2 sample males demonstrated a greater significance. In the class III sample, males also demonstrated more significance than females. CONCLUSION: Males with various sagittal skeletal malocclusions demonstrated a significant difference in lower soft tissue thickness (characterized as thicker lower facial soft tissue) compared to female patients in class I, class II division 1, class II division 2, and class III malocclusions.